Bivalves from the Chilean Fjords Region: Knowns and Unknowns - Güller, Marina (2015)
The Chilean Fjords Region has been regarded as one of the most complex coastal systems of the world, with a high level of mollusk diversity. Contradictorily, bivalves from this region have been recently considered both well and insufficiently known. This study critically evaluates the current state of knowledge on bivalves from the Chilean Fjords Region, by combining information coming from previously published literature, the study of material housed at museum collections, and new data coming from recently collected material. Although a total of 223 species appear listed in the literature for the area, only 81 valid species have documented records, the remaining corresponding to nomina dubia/nuda, synonyms, misidentifications, species complexes or species which were listed for the area, but based on unknown sources. The present study makes evident that, after more than two centuries the knowledge on bivalve diversity from the Chilean Fjords Region still remains at its first stages.